Boats as housing in Oxford, UK: Trajectories of Informality in a High-Income Context - Jakub Galuszka (International Journal of Urban and Regional Research, 2024)
In this article I aim to shed light on boat dwelling as an increasingly popular housing practice in the UK. I investigate the changing nature of this practice in times of housing crisis and of the connection between formal and informal approaches, and discuss how decentralized urban actors influence and safeguard their visions of housing. My investigation concentrates on three intertwined strategies boaters in Oxford use to deal with growing regularization and commodification pressures: (non)compliance, formalization and staying under the radar. My findings challenge several assumptions about housing informality in the global North and document the diverse trajectories that informal processes may take. My analysis reveals that informal and semi-formal solutions are not simply `tolerated' or `overlooked' by the state, but co-produced by urban dwellers through a repertoire of everyday actions and ad hoc advocacy approaches. The construction of specific trajectories of informal housing emerges at the interface of complex agendas and attitudes that go beyond the generalized roles attributed to the key urban sectors.
Keywords: 300; informality; formality; everyday approaches; advocacy; gentrification; co-production; precariousness; housing; waterways; houseboats